Frontier Fictions : Shaping the Iranian Nation, 1804-1946 - Kashani-Sabet, Firoozeh, 1967- (Book collections on Project MUSE., 1999)
"In Frontier Fictions, Firoozeh Kashani-Sabet looks at the efforts of Iranians to defend, if not expand, their borders in the nineteenth and early twentieth centuries, and explores how their conceptions of national geography influenced cultural and political change. The "frontier fictions," or the ways in which the Iranians viewed their often fluctuating borders and the conflicts surrounding them, played a dominant role in defining the nation. On these borderlands, new ideas of citizenship and nationality were unleashed, refining older ideas of ethnicity."--Jacket